A case of eosinophilic cystitis mimicking an invasive bladder cancer - Okazaki, Satoshi (Hinyokika kiyo. Acta urologica Japonica, 2014)
A 60-year-old woman was referred to our hospital because of gross hematuria, right lumbar pain and lower abdominal pain. Computed tomography (CT) scan revealed hydronephrosis of the right kidney, irregular bladder wall thickening at the right lateral and posterior portion and external iliac lymph node swelling of the right side. Laboratory data revealed disseminated intravascular coagulation syndrome (DIC) and eosinophilia. Because she developed a high fever that was caused by acute obstructive pyelonephritis of the right kidney, percutaneous nephrostomy was placed and the therapy for DIC was initiated. Pathological examination of transurethral resection of bladder tumor performed twice showed no malignancy but inflammatory infiltration of many eosinocytes, leading to the diagnosis of eosinophilic cystitis (EC). We considered the possibility of allergic reaction to the drugs she was taking as the etiology of EC and discontinued all drugs. Although eosinophilia was resolved afterward, she then developed brain infarction, followed by cerebral hemorrhage. She was transferred to a rehabilitation hospital for long-term care. CT scan that was performed 4 months after the initial presentation showed the resolution of hydronephrosis of the right kidney and external iliac lymph node swelling and the improvement of bladder wall thickness. Hydronephrosis of the right kidney has not recurred after removing the nephrostomy catheter. EC is a rare condition that could mimic an invasive bladder cancer. EC should be considered if bladder tumor is associated with eosinophilia. Therapeutic consideration for thromboembolic events should be made in patients with EC